Low-cost, scalable, and automated fluid sampling for fluidics applications. (October 2021) - Booeshaghi, A. Sina; Kil, Yeokyoung (Anne); Min, Kyung Hoi (Joseph); Gehring, Jase; Pachter, Lior
Graphical abstract: Abstract: We present colosseum, a low-cost, modular, and automated fluid sampling device for scalable fluidic applications. The colosseum fraction collector uses a single motor, can be built for less than $100 using off-the-shelf and 3D-printed components, and can be assembled in less than an hour. Build Instructions and source files are available at https://doi.org/10.5281/zenodo.4677604 .